Solution of Variavle Delay integral eqiations using Variational approach (Baghdad Science Journal, 2006)
The main objective of this research is to use the methods of calculus ???????? solving integral equations Altbataah When McCann slowdown is a function of time as the integral equation used in this research is a kind of Volterra